Molecular Survey on Kobuviruses in Domestic and Wild Ungulates From Northwestern Italian Alps - Barbara Di Martino (Frontiers in Veterinary Science, 2021)
Since the first identification in 1989 in humans, kobuviruses (KoVs) have been identified from a wide range of animal species including carnivores, rodents, birds, ungulates, rabbits, and bats. Several studies have described the identification of genetically related KoVs in the fecal virome of domestic and wild animals suggesting a mutual exchange of viruses. By screening a total of 231 fecal samples from wild and domestic ungulates, KoVs RNA was detected in wild boars (3.2%; 2/63), chamois (4.6%; 2/43), and goats (2.6%; 2/77). On phylogenetic analysis of the partial RdRp sequence, the wild boar strains clustered within the species Aichivirus C whilst the strains identified in domestic and wild ruminants grouped into the species Aichivirus B. The complete VP1 gene was obtained for chamois and goat KoVs. Interestingly, upon phylogenetic analysis the strains grouped together with a KoV of ovine origin within a distinct genetic type (B3) of the species Aichivirus B.